Influenza, pneumococcal, and COVID-19 vaccination coverage and hesitancy in adults with psychiatric disorders - Demir Pervane, Vasfiye; Uyar, Betül; Erten Bucaktepe, Pakize Gamze (Frontiers in Psychiatry, 2025)
Background/ObjectivesPatients with psychiatric disorders have high mortality and morbidity rates from infectious diseases, but low vaccination rates compared to the normal population. This study aimed to evaluate the vaccination rates for influenza, pneumococcal, and COVID-19 vaccines, and the levels of vaccine hesitancy among individuals with psychiatric disorders.MethodsThe study was a cross-sectional study among patients with psychiatric disorders. Participants’ vaccination statuses for influenza, pneumococcal, and COVID-19 vaccines during the pandemic were assessed, along with their vaccine hesitancy levels using a vaccine hesitancy scale. Data were collected between 01.03.2024 and 27.11.2024.ResultsThe study included 500 patients diagnosed with psychiatric disorders. Only 3.6% of the participants had received the influenza vaccine in the previous year, 3.0% reported regular influenza vaccinations, and 76.2% had received the COVID-19 vaccine during the pandemic. Among the participants at risk for pneumococcal infection (14%), the vaccination rate was only 2%. Patients with attention deficit hyperactivity disorder (ADHD) (45.0%) and anxiety disorder (17.2%) had the highest rates of regular influenza vaccination, while those with psychosis (13.6%) and depression (14.6%) had the lowest (p=0.010). COVID-19 vaccination rates during the pandemic were highest in ADHD (90.0%), bipolar disorder (81.1%), and depression (80.8%), and lowest in psychosis (54.5%) and obsessive-compulsive disorder (64.3%)(p=0.002). Women (p=0.001), participants with below university education levels (p=0.009), and patients with psychosis showed greater vaccine hesitancy. Patients with ADHD and bipolar disorder had the most positive attitudes toward vaccination (p=0.021). Positive attitudes were also linked to recent or regular influenza vaccinations and COVID-19 or pneumococcal vaccinations (p<0.05).ConclusionsLow vaccination rates and high vaccine hesitancy in psychiatric patients, particularly those with psychosis, necessitate targeted strategies to improve immunization coverage in this population.